(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In practice, a customer relationship management (CRM) system is considered as application software, which is designed for organizations and enterprises, with the aim of facilitating the organization and successful implementation of relationships with current and future customers, i.e. CRM systems are mainly referred to business. The purpose of this paper is to research and represent the integration/deployment and benefits of CRM-systems in non-profit organizations such as universities and other higher education institutions, thereby contributing to increasing their competitiveness. The appropriate communication and streamlined processes are the key steps to attracting and retaining more students, as well as staying competitive, therefore an adequate using of CRM system can support taking advantage of these success factors. The paper proposes a comparative analysis of existing leading CRM systems in the field of Higher Education, a summarization of the benefits and the need for their deployment.